Compensations and employee retention of an industrial company, Puente Piedra, 2022 - Tejeda-Arias, Luis Alberto (LACCEI, 2023)
The purpose of this research was to determine the relationship between compensations and employee retention (and its dimensions: professional development, work environment and salary structure) in an industrial company, Puente Piedra, 2023. For this research we used a quantitative approach methodology, applied type, correlational and descriptive level, non-experimental and cross-sectional design. We worked with a population of 90 people, which consisted of the company's workers. The study sample consisted of 74 workers of the company. The technique used was the survey. And the instrument used was the questionnaire which consisted of 28 items. It was concluded that compensation is significantly related to employee retention in an industrial company, Puente Piedra, 2023 (sig.=0.000; rho=0.889) as well as in its dimensions professional development, work environment and salary structure (sig.=0.000, rho=0.823; sig.=0.000, rho=0.787; sig.=0.000, rho=0.859; sig.=0.000, rho=0.775) respectively. Finally, conclusions and recommendations were issued.